2007
DOI: 10.1002/ajmg.c.30127
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal occlusion: A review of obstructing fetal lungs to make them grow and mature

Abstract: Fetal lung growth and functional differentiation are affected strongly by the extent that pulmonary tissue is distended (expanded) by liquid that naturally fills developing future airspaces. Methods that prevent normal egress of this lung fluid through the trachea magnify mechanical stretching of lung parenchymal cells, thereby promoting lung development. Indeed, experimental observations demonstrate that in utero tracheal occlusion (TO) performed on fetuses during the late canalicular-early saccular stage pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 118 publications
(194 reference statements)
2
77
0
2
Order By: Relevance
“…However, even after correction for gestational age at birth, early prenatal balloon removal improved the chances of survival. In animal experiments, cyclical or temporary occlusion has been shown to improve lung maturation 26,27,31 . This might also be the case clinically, although early morbidity parameters were unaffected by prenatal balloon removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even after correction for gestational age at birth, early prenatal balloon removal improved the chances of survival. In animal experiments, cyclical or temporary occlusion has been shown to improve lung maturation 26,27,31 . This might also be the case clinically, although early morbidity parameters were unaffected by prenatal balloon removal.…”
Section: Discussionmentioning
confidence: 99%
“…The FETO procedure has been described in detail 22,23,28 . Briefly it consists of the percutaneous fetoscopic insertion of a balloon into the fetal trachea, which in general is performed at approximately 26-28 (range, [23][24][25][26][27][28][29][30][31][32][33] weeks' gestation. The balloon is preferentially removed in utero at approximately 34 weeks by tracheoscopy or ultrasound-guided puncture.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly normal lung growth and maturation was achieved in sheep by a cyclical occlusion protocol, that is, a 47 h occlusion period altered by 1 h release, and this between 110 and 138 days (Nelson et al, 2005). For further details on these and other studies related to experimental tracheal occlusion, we refer to some comprehensive reviews (Nelson et al, 2006;Khan et al, 2007).…”
Section: History Of Experimental Fetal Surgery For Cdhmentioning
confidence: 99%
“…A number of animal studies have demonstrated that surgical tracheal occlusion applied during the canalicular and saccular stages of lung development not only improves dry lung weight but also increases airway branching, alveolarization, alveolar surface area, type II pneumocytes and pulmonary vascular growth (Khan, Cloutier, & Piedboeuf, 2007).…”
Section: Purpose Of In Utero Respiratory Movementsmentioning
confidence: 99%